Bank ratings: what determines their quality? - Harald Hau; Sam Langfield; David Marqués-Ibá\~nez (European Central Bank (ECB), 2012)
This paper examines the quality of credit ratings assigned to banks in Europe and the United States by the three largest rating agencies over the past two decades. We interpret credit ratings as relative assessments of creditworthiness, and define a new ordinal metric of rating error based on banks' expected default frequencies. Our results suggest that rating agencies assign more positive ratings to large banks and to those institutions more likely to provide the rating agency with additional securities rating business (as indicated by private structured credit origination activity). These competitive distortions are economically significant and contribute to perpetuate the existence of `too-big-to-fail' banks. We also show that, overall, differential risk weights recommended by the Basel accords for investment grade banks bear no significant relationship to empirical default probabilities.
Keywords: G21; G23; G28; 330; conflicts of interest; credit ratings; Prudential Regulation; rating agencies; Bank; Kreditwürdigkeit; Dienstleistungsqualität; Ratingagentur; USA; EU-Staaten